Evaluation of a pilot-scale bio-trickling filter as a VOCs control technology for the chemical fibre wastewater treatment plant. (15th September 2019) - Yang, Zhuhui; Li, Jian; Liu, Jia; Cao, Jingyang; Sheng, Dinghe; Cai, Tingjian
Abstract: The performance of lab- and pilot-scale bio-trickling filters (BTFs) for the treatment of emissions from a chemical fibre wastewater treatment plant was investigated. These systems were installed mainly to demonstrate the effectiveness of bio-trickling technologies in purifying exhaust gases containing different kinds of volatile organic compounds (VOCs). Results showed that 12 days more were necessary for the pilot-scale BTF to start up successfully than the lab-scale one. Both the lab- and pilot-scale BTFs exhibited contaminant removal efficiency higher than 90% at an empty bed residence time of 59 s, corresponding to gas flow of 0.2 m 3  h −1 and 550 m 3  h −1, respectively. The reduction of the microelement in the nutrient solution had little effect on the performance of the pilot-scale BTF. The abundance and diversity of the microorganism analysis showed that the diversity of the contaminants had a significant influence on the microorganism distribution in the BTF. Economic feasibility study showed that BTF might be an efficient solution for VOCs control with a lower cost than adsorption technology and regenerative catalytic oxidation. Highlights: The pilot-scale bio-trickling filter could treat the actual exhausts effectively. The bacterial community changed among different layers of the bio-trickling filter. Economic cost of bio-trickling filter was lower than adsorption and oxidation method.